Bacteria contamination of touch surfaces in Polish hospital wards - Anna Różańska; Dorota Romaniszyn; Agnieszka Chmielarczyk; Małgorzata Bulanda (Nofer Institute of Occupational Medicine, 2017)
Background: The objective of the study has been to evaluate the pathogenic bacteria contamination of touch surfaces in hospital wards. Material and Methods: Samples were taken from frequently touched surfaces in the hospital environment in 13 units of various types. Culturing was carried out on solid blood agar and in growth broth (tryptic soy broth - TSB). Species identification was performed using the analytical profile index (API) biochemical testing and confirmed with matrix assisted laser desorption ionization time-flight mass spectrometry (MALDI-TOF-MS) system. Results: The total of 161 samples were taken for the study. Fifty-two of them, after 24 h of culture on a solid medium, demonstrated bacterial growth and further 60 samples had growth after prior multiplication in TSB. Overall, 69.6% of samples exhibited growth of 19 bacterial species. Pathogenic species - representing indicator organisms of efficiency of hospital cleaning - was demonstrated by 21.4% of samples. Among them Acinetobacter spp., Enterocococci spp. and Staphylococcus aureus were identified. Coagulase-negative staphylococci (CNS) were predominant. The proportion of various groups of bacteria significantly varied in respective hospitals, and in various types of wards. Disturbing observation is a large proportion of resistance of isolated CNS strains as a potential reservoir of resistance genes. Conclusions: The results show that touch surfaces in hospital units are contaminated by both potentially pathogenic and pathogenic bacterial species. In connection with the reported, also in Poland, frequent omission or incorrect execution of hand hygiene by hospital staff, and probably patients, touch surfaces still constitute important reservoir of pathogenic bacteria. Improving hand hygiene compliance of health-care workers with recommendations is necessary for increasing biological safety of hospital environment. Med Pr 2017;68(3):459-467